1999:1 - Karl-Josef Kuschel; Jonas Alwall; Dorothea Rosenblad; Lena Petersson; Åke Andreasson; Ulf Sjögren; Aasulv Lande; Eva M. Hamberg (Svensk Teologisk Kvartalskrift, 2013)
FRÅN REDAKTIONEN Religionsmöte och religionsdialog